1981
DOI: 10.1126/science.6255566
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-4-Phosphonobutyric Acid: A New Pharmacological Tool for Retina Research

Abstract: Information processing in the vertebrate retina occurs in two separate channels known as ON and OFF channels. When intracellular electrophysiological recordings were obtained from the perfused retina-eyecup preparation of the mud-puppy (Necturus maculosus), the addition of 2-amino-4-phosphonobutyric acid to the bathing medium blocked all responses in the ON channel but left intact the OFF responses including OFF ganglion cell discharge. 2-Amino-4-phosphonobutyric acid blocks the light response of the ON bipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
456
2
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 780 publications
(486 citation statements)
references
References 19 publications
24
456
2
4
Order By: Relevance
“…Pharmacological agents, L-2-amino-4-phosphonobutyric acid (APB) (1.6 -2.0 mM) to eliminate on bipolar cell light responses (Slaughter and Miller, 1981), cis-2,3-piperidinedicarboxylic acid (PDA) (5.2 -6.2 mM) to block Off bipolar and inner retinal light responses (Slaughter and Miller, 1983;Massey, 1990 for review), and a mixed solution of APB +PDA (same concentrations as reported for each) were injected into the eye (1.0 -1.5 μl) using a Hamilton microsyringe. (Hamilton Company, Reno, NV).…”
Section: Intravitreal Injectionmentioning
confidence: 99%
“…Pharmacological agents, L-2-amino-4-phosphonobutyric acid (APB) (1.6 -2.0 mM) to eliminate on bipolar cell light responses (Slaughter and Miller, 1981), cis-2,3-piperidinedicarboxylic acid (PDA) (5.2 -6.2 mM) to block Off bipolar and inner retinal light responses (Slaughter and Miller, 1983;Massey, 1990 for review), and a mixed solution of APB +PDA (same concentrations as reported for each) were injected into the eye (1.0 -1.5 μl) using a Hamilton microsyringe. (Hamilton Company, Reno, NV).…”
Section: Intravitreal Injectionmentioning
confidence: 99%
“…In the mature retina, this glutamate agonist hyperpolarizes On bipolar cells and rod bipolar cells, thereby preventing their release of glutamate (Slaughter and Miller, 1981;Bolz et al, 1984;Müller et al, 1988). However, nothing is known about the effects of APB on the visual responses of developing retinal ganglion cells.…”
Section: Effects Of Apb Application On the Visual Responses Of Develomentioning
confidence: 99%
“…What underlies the gradual retraction of initially multistratified ganglion cell dendrites remains to be established. It has been shown, however, that treating the postnatal cat retina with the glutamate analog 2-amino-4-phosphonobutric acid (APB), which in the mature retina hyperpolarizes On-cone bipolar cells and rod bipolar cells thereby preventing their release of glutamate (Slaughter and Miller, 1981;Bolz et al, 1984;Müller et al, 1988), results in a much higher than normal incidence of ganglion cells with multistratified dendrites (Bodnarenko and Chalupa, 1993;Bodnarenko et al, 1995). Interestingly, it is not activity per se that shapes this developmental process because the formation of stratified ganglion cells is not perturbed by intraocular TTX injections (Dubin et al, 1986;Wong et al, 1991) or by visual deprivation (Leventhal and Hirsch, 1983;Lau et al, 1990).…”
mentioning
confidence: 99%
“…To test for a high tonic level of glutamate release, we measured the response in the membrane potential of an ON cell at several points after tonically hyperpolarizing the ON bipolar cell with the agonist of its metabotropic glutamate receptor (mGluR6), L-AP-4 (25-50 m; Shiells et al, 1981;Slaughter and Miller, 1981). L-AP-4 hyperpolarized the membrane potential and reduced the variance of the membrane potential (Fig.…”
Section: Polarizing the Cell Altered Rectification Of Spiking Responsesmentioning
confidence: 99%
“…The balance between ON and OFF cells can be disturbed by injecting L-AP-4 into the eye to hyperpolarize ON bipolar cells and therefore to block the output of ON ganglion cells (Shiells et al, 1981;Slaughter and Miller, 1981;Schiller, 1982). ON pathway blockade alters the receptive field properties of cortical cells and reduces psychophysical sensitivity to contrast, especially for a stimulus brighter than the background (Schiller, 1982;Sherk and Horton, 1984;Schiller et al, 1986;Dolan and Schiller, 1994).…”
Section: Introductionmentioning
confidence: 99%